BERPIKIR KOMPUTASI SISWA DALAM MENINGKATKAN PEMBELAJARAN: STUDI LITERATUR: Students' Computational Thinking In Improving Learning: Literature Study - Sastika, Weni; Yahfizham, Yahfizham (Al-Aqlu: Jurnal Matematika, Teknik dan Sains, 2024)
The purpose of this study is to provide a study on the thinking process to improve the learning process. This research uses a research method obtained from the publication of research articles in scientific journals previously. It includes three stages: setting, synthesizing, and identifying. Based on the results obtained, mathematics is a subject that can introduce and develop computational thinking skills in students.